Evaluation of the Effectiveness of Drying Groundnuts (Arachis hypogaea) on Post-Harvest Losses: A Case Study of Khwisero Sub-County, Kenya - Kirui, S. K.; Some , D. K.; Mutai, E. B. K. (Africa Environmental Review Journal, 2022)
Loss of grains through mould infection is a serious problem for farmers in rural societies. Solar drying of groundnuts offers a huge potential to reduce Aflatoxin contamination. The purpose of this study was to assess the effectiveness of drying groundnuts on post-harvest losses in Kenya. The investigation was guided by the following specific objectives: To characterize the physical characteristics of various groundnut varieties in Khwisero Sub-County, Kenya; to characterize the drying technologies existing in the Sub-County, Kenya and to evaluate the performance of the existing drying technologies in the Sub-County. The study adopted a factorial experimental design. In this study parameters included; temperature, relative humidity, moisture content, drying time, and drying rate. The groundnuts for experimental purposes were acquired through purposive sampling. Data was collected using data loggers, a data sheet, and a household survey. The following physical properties of groundnut grains were evaluated; surface area, bulk density, and porosity. To evaluate the efficiency of the existing dryer designs for effective drying of groundnuts, the effectiveness of each drier was determined the following parameters; drying time, drying rate, moisture content, temperature, and relative humidity. The drying technologies under study were open sun drying, the greenhouse effect, and the modified greenhouse effect. The open sun drying depended on the natural weather while the Greenhouse and the modified greenhouse effect offered the opportunity for the farmers to dry their kernels in any circumstance of weather or duration e.g. sunny, rainy, or cloudy weather, in the day or at night when temperatures are colder with energy reaching the surface of 678 kWh/m2. It is critical to dry harvested groundnuts correctly, as improper drying can promote fungal growth and reduce kernel quality for consumption and propagation.